A Case of Xanthogranulomatous Pyelonephritis Associated with Renoduodenal Fistula - R. Conor Holton-Burke; Mini Varughese (Case Reports in Medicine)
Xanthogranulomatous pyelonephritis (XGP) is a rare form of pyelonephritis associated with repeated infection, chronic inflammation, and obstruction. Various fistulas, including those to the intestine, are a known association with XGP. Here, a 55-year-old woman with a history of multiple previous renal calculi presented with dysuria and back pain. Contrast-enhanced computed tomography (CT) revealed a soft tissue density in her renal pelvis and perirenal space consistent with XGP along with a tract connecting the upper pole of her right kidney to the second portion of the duodenum. This finding was subsequently confirmed during percutaneous nephrostomy placement, stent placement, a small bowel follow-through study, and upper endoscopy. She was diagnosed with XGP with associated renoduodenal fistula, eventually treated by open nephrectomy with fistula takedown. Histopathologic analysis was consistent with the diagnosis of XGP with no malignant or infectious cause of the fistula. XGP should be considered in the diagnosis of patients with dysuria and back pain, especially when a history of obstruction or chronic inflammation. Associated fistulas should also be considered prior to surgical management to prevent complications.